Institutional Governance System (IGS) for forest management planning: A theoretical proposal - Sicco Dany Dogmo Pokem (Albert-Ludwigs-Universität Freiburg, Institut für Forstökonomie, 2008)
The structure of this working paper is as follows. In the first part after the introduction, the theory underlying the IGS is discussed (Chapter 2); specifically the conceptual framework for which the IGS of a forest management planning design can be developed. Five concepts are discussed here, namely the rationalist view of forest planning versus the community based view of planning on the one hand, and the "common", the "co-management" and the participatory and conflict management concept on the other. Then, based on the problem resulting from these five theories, the next section addresses the need for a new approach in forest planning. The second part of this working report emphasises the design of the institutional governance system (IGS), built primarily on the basis of the 'institutional analysis and development (IAD) framework' developed by Ostrom and colleagues.31 This approach facilitates the analysis of the actors' interactions and incentives in a given forest planning process (chapter 3). The IGS also incorporates interactive and active participatory forest planning and conflict management (democratic resolution of a problem) based on the establishment of a working group called the Combined Planning System Working Group (CPSWG), and also communication/consultation, negotiation and consensus building (Chapter 4). The third part of this report highlights the conclusions of the study (Chapter 5).
Keywords: 330; Forstpolitik; Nachhaltige Entwicklung; Forstökonomie; Institutionelle Infrastruktur; Governance-Ansatz; Theorie; Kamerun